THU0384 Classification of Systemic Lupus Erythematosus Patients by Expression Pattern of Immune and Disease-Associated Genes in Peripheral Blood. (9th June 2015) - Kurasawa, T.; Suzuki, K.; Kikuchi, J.; Miyoshi, F.; Mogami, A.; Kojima, S.; Hisada, Y.; Yoshimoto, K.; Kaneko, Y.; Yasuoka, H.; Yamaoka, K.; Takeuchi, T.
Abstract : Background: Gene expression analysis in SLE patients with peripheral blood have identified activated type I interferon signature by DNA microarray (1, 2) and RNAseq (3). However, the link between detailed and comprehensive information at the molecular level and clinical manifestation and/or laboratory parameters remains unclear. In addition, it also remains unclear exactly how we should utilize this information for better understanding of pathophysiology in individual patient. Objectives: Clarify the significant association between gene expression and clinical data and establish a means of classifying patients by expression patterns of immune and disease-associated genes. Methods: Total RNA was purified from peripheral blood: 13 active SLE patients, 5 healthy controls (HC)). Quantitative gene expression data were collected by the latest high density DNA microarray (Human 8X60k ver.2.1, Agilent technologies) and analyzed by several bioinformatics methods. Results: All patients were female and mean age was 45 years. Disease activity was high (SLEDAI: 16.5±7.5 (Mean ± SD). Differentially expressed gene analysis statistically identified 558 up-regulated and 289 down-regulated genes including non-coding RNA as compared with HC (P<0.05, t-test). Stratification analysis classified by presence or absence of renal involvement purified lupus nephritis associated 14 genes (10 up-regulated and 4 down-regulated) including RTKN2 although stratification by autoantibody, disease activity or treatment could not purify any gene. Next, we calculated the correlation between all gene expression data and 50 clinical parameters and identified that serum LDH and urine β2-microglobulin strongly associate with the overall change of gene expression whereas serum CRP, autoantibody and SLEDAI do not. These findings may suggest that LDH and β2-microglobulin but not CRP may reflect peripheral blood cell injury due to the activity of SLE. We further classified SLE patients and HCs by clustering analysis using gene lists: plasmablast (number of genes: 12, Figure ), proteasome (55), and interferon (27) associated and SLE susceptibility (57) genes. Plasmablast, proteasome and interferon associated gene lists efficiently enriched SLE patients without precondition, however SLE susceptibility gene list did not. Conclusions: Gene expression analysis focusing on its association to clinical data demonstrated that changes at the molecular level could reflect changes in clinical status of SLE patients. SLE patients had heterogeneous and unique characteristics from the aspect of immune associated gene expression. Our approach may aid physicians in determining treatment strategies for individual SLE patients. References: Kirou KA et. al. Arthritis Rheum. 2004;50: 3958-67 Higgs BW et.al. Ann Rheum Dis. 2011;70: 2029-36 Suzuki K et.al. Ann Rheum Dis. 2014;73(suppl2): 347 Disclosure of Interest: T. Kurasawa: None declared, K. Suzuki Grant/research support from: Eisai Co.Ltd. and Bristol-Myers Squibb Company, J. Kikuchi: None declared, F. Miyoshi Employee of: Mitsubishi Tanabe Pharma Corporation, A. Mogami Employee of: Mitsubishi Tanabe Pharma Corporation, S. Kojima Employee of: Mitsubishi Tanabe Pharma Corporation, Y. Hisada Employee of: Mitsubishi Tanabe Pharma Corporation, K. Yoshimoto: None declared, Y. Kaneko Consultant for: Abbvie, Paid instructor for: Eisai Pharmaceutical, Chugai Pharmaceutical, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Janssen, UCB, H. Yasuoka Paid instructor for: Abbvie, K. Yamaoka Consultant for: Pfizer, Speakers bureau: Pfizer, Chugai Pharma, Mitsubishi-Tanabe Pharma, Takeda Industrial Pharma, GlaxoSmithKline, Nippon Shinyaku, Eli Lilly, Janssen Pharma, Eisai Pharma, Astellas Pharma and Actelion Pharmaceuticals, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Paid instructor for: Mitsubishi Tanabe Pharma Co., Eisai Co., Ltd., Abbivie GK, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co.Ltd